Respuesta :
Given the equation:
(1) [tex]-2=-x+ x^{2}-4[/tex]
We need to find a, b and c. So, we know that a quadratic equation is given by:
(2) [tex]ax^{2}+bx+c=0[/tex]
Then, we need to order the equation (1) and to adjust it to the equation (2), so:
[tex]x^{2}-x-2=0[/tex]
So, if we compare these two equations, the conclusion is:
[tex]a=1[/tex]
[tex]b=-1[/tex]
[tex]c=-2[/tex]
(3) [tex]x= \frac{-b\pm \sqrt{b^{2}-4ac}}{2a}[/tex]
Substituiting a, b and c into (3):
[tex]x= \frac{-(-1)\pm \sqrt{(-1)^{2}-4(1)(-2)}}{2(1)}[/tex]
Finally, the results are two values:
[tex]x_{1}=2[/tex]
[tex]x_{2}=-1[/tex]
(1) [tex]-2=-x+ x^{2}-4[/tex]
We need to find a, b and c. So, we know that a quadratic equation is given by:
(2) [tex]ax^{2}+bx+c=0[/tex]
Then, we need to order the equation (1) and to adjust it to the equation (2), so:
[tex]x^{2}-x-2=0[/tex]
So, if we compare these two equations, the conclusion is:
[tex]a=1[/tex]
[tex]b=-1[/tex]
[tex]c=-2[/tex]
(3) [tex]x= \frac{-b\pm \sqrt{b^{2}-4ac}}{2a}[/tex]
Substituiting a, b and c into (3):
[tex]x= \frac{-(-1)\pm \sqrt{(-1)^{2}-4(1)(-2)}}{2(1)}[/tex]
Finally, the results are two values:
[tex]x_{1}=2[/tex]
[tex]x_{2}=-1[/tex]
The correct substitution of a, b and c in the quadratic formula is as follows:
[tex]\frac{-(-1) +\sqrt{(-1)^{2}-4(1)(-2) } }{2(1)}[/tex]
Quadratic equation
The quadratic equation follows the pattern,
- ax² + bx + c
The given equation have to b arrange in the format above to know the value of a, b and c.
Therefore,
-2 = -x + x²- 4
x² - x - 4 +2 = 0
x² - x - 2
Therefore,
a = 1
b = -1
c = -2
Using the quadratic formula
[tex]\frac{-b +\sqrt{b^{2}-4ac } }{2a}[/tex]
The correct substitution is as follows
[tex]\frac{-(-1) +\sqrt{(-1)^{2}-4(1)(-2) } }{2(1)}[/tex]
learn more on quadratic equation here: https://brainly.com/question/9634215